(untitled) (Sebha University Conference Proceedings, 2024)
This study aimed to investigate the impact of risk management implementation on reducing organizational losses and to assess the effectiveness of risk management practices within an organization. A descriptive-analytical approach was employed, with a questionnaire as the primary data collection tool. A simple random sample of 230 individuals was selected from the study population and analyzed using SPSS statistical software. The findings revealed several significant results: * Senior management recognizes the importance of risk management in reducing organizational losses. * Effective procedures and policies are in place to mitigate risks and minimize potential losses. * Risks are monitored regularly and reported to senior management in a timely manner. * The implementation of risk management has a positive impact on reducing organizational losses. Based on these findings, the study recommends allocating sufficient human, financial, and technical resources to effectively implement risk management within the organization. Additionally, improving environmental management systems to reduce environmental pollution losses is suggested. Note: * Clarity and Conciseness: The translation aims to maintain the original meaning while using clear and concise language. * Technical Terms: Technical terms related to risk management and statistical analysis have been translated accurately. * Style and Tone: The tone of the original abstract has been preserved, ensuring a formal and academic style.